Editorial: Perspectives on energy futures, environment and wellbeing - Ulgiati, Sergio (2019)
“We tend to think of development, not in terms of evolution, but interms of creation. [...] If we talk of promoting development, whathave we in mind: goods or people?”(Schumaker, 1989)Schumaker (1989)raises doubts about whether the so-called soci-etal development is oriented to an individual and/or collective evolu-tion in its deeper meaning, or oriented to material creation. Develop-ment is a widely used term mostly without establishing a properlysemantic, usually to sustain the business-as-usual production-con-sumption behavior claimed as mandatory to societal development.However, the ultimate goal of such behavior is to keep with the ma-terial flow and increase the gross economic product rather than a de-velopment focused on evolution of human beings in their complexfeatures. Such a production-consumption pattern causes pressure onenergy and environmental security (as a provider of resources and re-ceiver of sub products for dilution), which deserves special attention bypolicy makers when promoting societal development. Currently, energypolicies are demanding a reduction in greenhouse gases and toxicemissions, because increased development based on resource ...